2015
DOI: 10.1080/13102818.2015.1006413
|View full text |Cite
|
Sign up to set email alerts
|

Research into acetone removal from air by biofiltration using a biofilter with straight structure plates

Abstract: The biological air treatment method is based on the biological destruction of organic compounds using certain cultures of microorganisms. This method is simple and may be applied in many branches of industry. The main element of biological air treatment devices is a filter charge. Tests were carried out using a new-generation laboratory air purifier with a plate structure. This purifier is called biofilter. The biofilter has a special system for packing material humidification which does not require additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Among them, one is strictly aerobic ( B. siralis ), while the others are facultative anaerobic. Bacillus species have already been observed in biofilters treating VOCs, including methanol . Nevertheless, this is the first identification of B. siralis in a biofilter.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Among them, one is strictly aerobic ( B. siralis ), while the others are facultative anaerobic. Bacillus species have already been observed in biofilters treating VOCs, including methanol . Nevertheless, this is the first identification of B. siralis in a biofilter.…”
Section: Resultsmentioning
confidence: 77%
“…Whereas, Paenibacillaceae have already been observed in air biofilters, Paenibacillus typhae , recently isolated (in 2013), has no environmental application so far. Among the Staphylococcus identified, S. aureus has been encountered in biofilters treating acetone …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental research revealed it was a rather efficient method for air cleaning. The efficiency of the filter for cleaning the air from a mixture of volatile organic compounds (VOCs) (butilacetate, butanol and xylene) at the permitted concentrations reached up to 70%-98% [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%